Praktik Akuntabilitas dan Kompetensi Sumber Daya Manusia terhadap Fraud Pengelolaan Dana Desa Dengan Moral Sensivity Sebagai Variabel Moderasi - Yuska Rahayu Djunaidi; Ayu Rakhma Wuryandini; Nurharyati Panigoro (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of this research is to analyze the factors that influence Village Fund Management Fraud with Moral Sensitivity as a moderating variable. This type of research is a descriptive quantitative method with a Multiple Regression Analysis (MRA) approach. In data collection techniques, researchers used surveys and distributed questionnaires in Kabila Bone District, where the research population consisted of nine villages spread across Kabila Bone District as the coastal area of ​​Tomini Bay. The sampling technique used purposive sampling with a research sample of 72 respondents. The results of this research show that Accountability Practices have a positive effect on village fund management fraud, Human Resource Competence has an effect on village fund management fraud, accountability practices and human resource competency have an effect on village fund management fraud, moral sensitivity is unable to moderate accountability practices on village fund management fraud, and moral sensitivity is able to moderate human resource competence towards village fund management fraud and is a quasi moderator